Touchdown trouble - Bowen, Fred (Peachtree, 2009)
Sam is proud that his touchdown in the final play of a game left his football team undefeated, but when a videorecording of the game reveals that the touchdown was scored illegally, he and the other Cowboys must decide whether to reveal the truth. Includes facts about a similar situation faced by Cornell University's team after a game with Dartmouth in 1940.